PENAMBAHAN KARAKTER LUAS PERMUKAAN DAN UKURAN PORI ARANG SEBAGAI UPAYA DIVERSIFIKASI PRODUK ARANG DARI TEMPURUNG KELAPA PADA CV. SOLO BUTTON - Yuniawan Hidayat; IF Nurcahyo; Fitria Rahmawati; Eddy Heraldy; Khoirina Dwi N; Witri Wahyu Lestari (Jurnal Kewirausahaan dan Bisnis, 2019)
At the factory of CV. Solo Button, coconut shell charcoal is made by heating the raw material in the open concrete reactor. This simple process results in minimal surface area characteristics and pore size, so the chrocoal is less suitable for the use as an adsorbent. Addition of treatment with degassing using N2 at temperatures of 200 oC and 300 oC can increase surface area, pore size and number of pore charcoal. The SAA and BET analysis showed an increase in surface area of 6.2% and 93.6% as well as an increased pore size of 14.5% and 12.29% at both temperatures. Adsorption-desorption graphs indicate that the untreated charcoal has uneven surfaces and the pores are not detected while the degassing treatment at these temperatures indicates the formation of micropores from the charcoal.Keywords: chrocoal, pore, surface area, coconut shell